2017
DOI: 10.1097/tp.0000000000001589
|View full text |Cite
|
Sign up to set email alerts
|

Belatacept Compared With Tacrolimus for Kidney Transplantation

Abstract: Background While tacrolimus is the basis of most maintenance immunosuppression regimens for kidney transplantation, concerns about toxicity have made alternative agents, such as belatacept, attractive to clinicians. However, limited data exists to directly compare outcomes with belatacept-based regimens to tacrolimus. Methods We performed a propensity score matched cohort study of adult kidney transplant recipients transplanted between May 1, 2001 and December 31, 2015 using national transplant registry data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Indeed, we observed that the efficacy of CTLA4-Ig was inferior in recipients that were more recently sensitized and harbored higher levels of DSA. In initial trials with belatacept that involved nonsensitized recipients and current clinical use involving patients that do not meet this stringent criteria, higher rates of acute rejection have been reported (2,34,(57)(58)(59). Thus, we consider the more stringent model with low levels of circulating DSA an excellent model to investigate CTLA4-Ig efficacy.…”
Section: Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we observed that the efficacy of CTLA4-Ig was inferior in recipients that were more recently sensitized and harbored higher levels of DSA. In initial trials with belatacept that involved nonsensitized recipients and current clinical use involving patients that do not meet this stringent criteria, higher rates of acute rejection have been reported (2,34,(57)(58)(59). Thus, we consider the more stringent model with low levels of circulating DSA an excellent model to investigate CTLA4-Ig efficacy.…”
Section: Cd4mentioning
confidence: 99%
“…Indeed, the accumulation of CD4 + and CD8 + T cells in the allograft was further reduced in the combination therapy group compared with monotherapy groups, and approached numbers that were comparable to naive tolerant allografts ( Figure 6A). We also tested whether FTY720 plus CTLA4-Ig reduced donor-specific infiltrating T cells by using sensitized mice that harbored, from the time of donor spleen cell sensitization, a tracer population of donor-reactive T cell receptor-transgenic TCR75 cells (1,000-2,000 cells/mouse) with specificity for donor-derived peptide (K d [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] ) presented on recipient I-A b . We similarly observed that the combination FTY720 plus CTLA4-Ig significantly decreased the numbers of TCR75 cells (which were predominantly CD44 + CD62L -) infiltrating the allografts compared with CTLA4-Ig monotherapy ( Figure 6B).…”
Section: Ctla4-ig Fails To Inhibit the Accumulation Of T Cells Into Tmentioning
confidence: 99%
“…The comparison between belatacept and tacrolimus therapy has also been investigated in three indirect studies [48][49][50]. In a single-center, retrospective analysis, the outcomes of KTRs treated with belatacept (n = 97) were compared with a historical cohort of patients treated with tacrolimus (n = 205) [48].…”
Section: Clinical Outcomes Of De Novo Use Of Belatacept In Kidney Tramentioning
confidence: 99%
“…CD4 1 CD57 1 T cells were also found to infiltrate the kidney allograft during rejection, and genes involved in allograft rejection were up-regulated in this T cell subset [20]. However, these findings were not confirmed in recent randomized controlled clinical trials in which belataceptbased immunosuppressive therapy was compared with tacrolimus-based immunosuppressive therapy [21][22][23]. In the study by de Graav et al, 11 of the 20 (55%) belatacepttreated patients experienced biopsy-proven acute rejection (BPAR) compared with two of 20 in the control arm [12,23], while in another study patient enrolment was even halted because of a high rate of acute cellular rejection [21].…”
Section: Introductionmentioning
confidence: 99%
“…These authors also demonstrated that, after polyclonal stimulation, CD4 1 CD57 1 PD-1 -T cells produced high levels of the effector cytokines interferon (IFN)-g or tumour necrosis factor (TNF)-a, or exhibited cytotoxicity [20]. However, these findings were not confirmed in recent randomized controlled clinical trials in which belataceptbased immunosuppressive therapy was compared with tacrolimus-based immunosuppressive therapy [21][22][23]. However, these findings were not confirmed in recent randomized controlled clinical trials in which belataceptbased immunosuppressive therapy was compared with tacrolimus-based immunosuppressive therapy [21][22][23].…”
Section: Introductionmentioning
confidence: 99%